Natural Science Education, Indigenous Knowledge, and Sustainable Development in Rural and Urban Schools in Kenya - O’Hern, Darren M. author. aut Link
XIV, 162 p.
Keywords: Through a multi-sited qualitative study of three Kenyan secondary schools in rural Taita Hills and urban Nairobi, the volume explores the ways the dichotomy between “Western” and “indigenous” knowledge operates in Kenyan education. In particular, it examines views on natural sciences expressed by the students, teachers, the state’s curricula documents, and schools’ exam-oriented pedagogical approaches. O’Hern and Nozaki question state and local education policies and practices as they relate to natural science subjects such as agriculture, biology, and geography and their dismissal of indigenous knowledge about environment, nature, and sustainable development. They suggest the need to develop critical postcolonial curriculum policies and practices of science education to overcome knowledge-oriented binaries, emphasize sustainable development, and address the problems of inequality, the center and periphery divide, and social, cultural, and environmental injustices in Kenya and, by implication, elsewhere. “In an era of environmental crisis and devastation, education that supports sustainability and survival of our planet is needed. Within a broader sociopolitical context of post-colonialism and globalization, this volume points out possibilities and challenges to achieve such an education. The authors propose a critical, postcolonial approach that acknowledges the contextual and situational production of all knowledge, and that de-dichotomizes indigenous from ‘Western’ scientific knowledge.” Eric (Rico) Gutstein, Professor, Curriculum and Instruction, University of Illinois at Chicago (USA).